Tanjung Desa Adat, Budaya, dan Pesona Alamnya - Reski Seftiyansyah; Zariul Antosa; Firdaus Ardiansyah; Ashila Devta Azalia; Fina Fitri Aisyah; Sherly Adelia; Bella Asyura; Olivia Asyfaa Ramadhani; Arkaan Fadhlullah; Aanisah Sesmawati; Arya Hadi Ghifary (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
This study analyzes the existence of Tanjung Village which is one of the traditional villages in Kampar Regency. In a traditional village, of course, there are customary law communities and also customary law that have strong correlations and ties. The people of Tanjung Village still maintain the basic cultural values ​​they have and are believed to be in the midst of the progress of civilization that is happening around them. Besides being rich in customs and culture, the natural charm found in this village is no less great. The natural charm that is still beautiful and preserved is sure to amaze the eyes of the public when visiting there.